2014
DOI: 10.3892/mco.2014.257
|View full text |Cite
|
Sign up to set email alerts
|

Elastofibroma dorsi: Surgical indications and complications of a rare soft tissue tumor

Abstract: Abstract. Elastofibroma dorsi (ED) is a tumor that develops in the space between the lower angle of the scapula and the posterior thoracic wall. Due to the rarity of this type of tumor, the number of reported consecutive series is limited. Surgical excision, usually recommended for symptomatic cases to confirm diagnosis and relieve symptoms, has been associated with a high complication rate. To analyze the clinical characteristics and outcomes of surgical treatment, we retrospectively reviewed 20 consecutive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 18 publications
1
34
1
Order By: Relevance
“…The most common postoperative complications in previous series have been haematomas and seromas, at rates of up to 40% and 86%, respectively. 7,13,19,20 The complication rates in our series were lower (10.5% and 26.3%), although an apparently larger rate in other series may be related to the smaller patient numbers. Elastofibromas should be excised in a marginal fashion, and our institution has no experience of local recurrence following excision.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…The most common postoperative complications in previous series have been haematomas and seromas, at rates of up to 40% and 86%, respectively. 7,13,19,20 The complication rates in our series were lower (10.5% and 26.3%), although an apparently larger rate in other series may be related to the smaller patient numbers. Elastofibromas should be excised in a marginal fashion, and our institution has no experience of local recurrence following excision.…”
Section: Discussionmentioning
confidence: 47%
“…The median tumour diameter of 8.2cm and median age at presentation of 66 years in our cohort mirrors that of previous case series. 5,13 The diagnosis of elastofibroma may be suggested by the characteristic symptom of 'clunking' on abduction and adduction of the arm. This was present in less than 60% of our patients, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was later observed that the condition could develop among people that do not do heavy labor, and in different localizations. The later publications argued that reactive fibromatosis, degeneration due to vascular insufficiency, elastotic degeneration, enzyme defects and systemic involvement could play a role in the pathogenesis [3,8,11]. In addition, Nagamine et al emphasized that there could be a genetic predisposition to etiology, because of the fact that they detected positive family history in 32% of the 170 cases in their study [3].…”
Section: Discussionmentioning
confidence: 99%
“…However, MRI findings are often sufficient for diagnosis [6]. The disease is frequently treated by the excision of the mass [7,8]. Total excision is necessary to prevent recurrence and to relieve pain [9].…”
mentioning
confidence: 99%